Development of robust and facile purification process for production of recombinant human ferritin heavy chain nanoparticle from Escherichia coli. (May 2021) - Song, Xiaotong; Zheng, Yongxiang; Zhu, Ling; Zhang, Li; Meng, Huan; Yu, Rong; Zhang, Chun
Graphical abstract: Highlights: The recombinant human ferritin heavy chain (rhFTH) was expressed and self-assembled in E. coli . Non-chromatographic procedure with optimized pH, temperature and NaCl was critical to the purity of rhFTH. rhFTH with intact nanoparticle structure was obtained with high recovery. Abstract: Recombinant human ferritin heavy chain (rhFTH) was highly expressed and self-assembled in E. coli bacteria. To establish a robust purification scheme, we developed a non-chromatographic precipitation procedure as a key step for extracting rhFTH from the disrupted supernatant. Three factors including heating temperature, pH value and sodium chloride concentration were systematically investigated and optimized for this precipitation procedure. Almost all of the unrelated proteins could be efficiently removed by the optimized precipitation procedure. Combining with hydrophobic interaction chromatography of Capto Butyl, the rhFTH was efficiently purified from the post-precipitated supernatant, the purity of the finally obtained rhFTH was above 98 % and the target protein recovery was around 66 % roughly estimated by optical density. ESI-MS analysis showed a molecular weight of 21086.0 Da that was almost identical with the theoretical value. Circular dichroism analysis revealed alpha-helix structure as major structure content and fluorescence analysis demonstrated that aromatic amino acids residues were highly buried inside. HP-SEC analysis showed a geometrically symmetrical peak, indicating rhFTH exists as homogeneous structure with a relatively large size, and further being validated by DLS and TEM. DSC analysis revealed that the extreme stability against temperature contributed mainly to the feasibility of the developed precipitation treatment.